Making the most of climate impacts ensembles - Challinor, Andrew J.; Martre, Pierre; Asseng, Senthold; Thornton, Philip K.; Ewert, Frank (Springer, 2014)
Increasing use of regionally and globally oriented impacts studies, coordinated across international modelling groups, promises to bring about a new era in climate impacts research. Coordinated cycles of model improvement and projection are needed to make the most of this potential.